A bibliometric analysis: navigating publication trends in academic dishonesty in higher education - Suraya Ahmad; Noor Emilina Mohd Nasir; Syafiq Abdul Haris Halmi; Nur Syuhada Adnan (Penerbit Universiti Kebangsaan Malaysia, 2024)
The spread of artificial intelligence poses threats to academic activities. Higher education institutions are aware of academic dishonesty among students and lecturers but cannot offer promising solutions to this problem. This study examines the publication trends, leading authors and nations, international collaboration and research topics on academic dishonesty in higher education published between the year 2001 and 2023. It identifies the main countries contributing research on academic dishonesty. The study utilizes bibliometric analysis of 239 articles from the Scopus database using TITLE-ABS-KEY approach. Microsoft Excel is used in analyzing the frequency of published materials using tables and charts. Additionally, the VOSviewer software is used to create bibliometric networks and Harzing’s Publish or Perish software is used to assess the citation metrics of the articles. The analysis shows that the number of publications on academic dishonesty is increasing, especially between the year 2020 and 2022. The articles were cited 4129 times, which corresponds to an average of 17.28 citations per article. The results show that the most common keywords discussed are academic dishonesty, higher education, cheating, students, and e-learning, which can be grouped into 5 clusters. The United States, Malaysia, South Africa, the United Kingdom, and Australia are among the countries that contribute to publications in this area. This study delves into publication trends on academic dishonesty, offering valuable insights into the current research landscape in higher education. By identifying key areas of focus and prominent research contributors, this analysis informs future research efforts aimed at mitigating this pervasive challenge.